The Marsupial Database: A comprehensive dataset on the ecology and life history of American and Australasian marsupials - Mariana Silva Ferreira; Rodrigo C. Rossi; Stephane Batista; Kathleen Sena; Kevin R. Bairos‐Novak; Shamia Farhana Shoma; Natália O. Leiner; Diego Astúa; Graeme Coulson; Diana O. Fisher; Natasha D. Harrison; Julian Nicholas Garcia Willmer; et al. (Ecology, 2026)
Marsupials are an important but typically neglected group of mammals that have been overlooked in many comparative analyses of vertebrate ecology and life history evolution. In order to address this knowledge bias, we have developed The Marsupial Database. The Marsupial Database contains traits for a phylogenetically diverse set of 414 extant and recently extinct (last 200 years) species from all seven modern marsupial orders (Dasyuromorphia, Didelphimorphia, Diprotodontia, Microbiotheria, Notoryctemorphia, Paucituberculata, Peramelemorphia) native to 34 countries in the Americas and Australasia. The database comprises 11,054 records of 35 traits describing anatomical, physiological, phenological, and reproductive characteristics, as well as information on species' ecology and current conservation status. Data were collected from 41 sources, comprising published databases and other relevant sources of information. By providing a centralized repository of marsupial ecological and life history traits, The Marsupial Database facilitates analyses of ecological and evolutionary patterns within the group, and also encourages inclusion of marsupials in comparative studies of mammals, vertebrates, and the entire animal kingdom. The Marsupial Database is free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.